PERLINDUNGAN HUKUM TERHADAP NASABAH FINTECH PEER TO PEER LENDING DALAM KAITANNYA PELANGGARAN PRIVASI - Rusmini Rusmini; Juniar Hartikasari; Husnaini Husnaini (Justici, 2023)
ABSTRACT The progress of the digital world has developed at this time, one of which is regarding the method of payment which was originally only with cash turned into cashless or e-money, shopping that was previously face-to-face between sellers and buyers can now be done online. The Government through Bank Indonesia and the Financial Services Authority as the agency authorized to regulate Financial Technology. In its development, many fintechs have had problems, both legal fintech and illegal fintech because they are not in accordance with government regulations. Legal protection is an illustration of the working of legal functions to realize legal goals. The problem in this paper is how the government's role in protecting fintech customers in Indonesia is. This research is a normative juridical research, which only examines library materials or secondary data, which may include primary, secondary and tertiary legal materials. Increasing the effectiveness of financial inclusion programs for people who are not yet bankable and MSME actors as well as consumer protection are also important things to be developed. The program issued by the OJK will support the financial inclusion program issued by the Government. The OJK's consumer protection function will also be implemented in a balanced manner between the interests of consumers and the interests of the financial services sector. So that the protection of customers or consumers continues to be carried out properly without any party feeling aggrieved. The government in this case the Minister of Finance has made regulations related to financial services and so on which are contained in the Regulation of the Minister of Finance (PMK).